Handbook of corporate finance : empirical corporate finance - Eckbo, Bjrn Espen (Handbooks in finance., 2008)
The empirical analysis of firms' financing and investment decisions-empirical corporate finance-has become a dominant field in financial economics. The growing interest in everything "corporate" is fueled by a healthy combination of fundamental theoretical developments and recent widespread access to large transactional data bases. A less scientific-but nevertheless important-source of inspiration is a growing awareness of the important social implications of corporate behavior and governance. *Takes stock of the main empirical findings to date across an unprecedented spectrum of corporate finance issues *Discusses everything from econometric methodology, to raising capital and capital structure choice, and to managerial incentives and corporate investment behavior. *Contributors are leading empirical researchers that remain active in their respective areas of expertise *Writing style makes the chapters accessible to industry practitioners